Penerapan Pendekatan STEM untuk Meningkatkan Kemampuan Kolaborasi dan Literasi Sains Siswa Kelas V Sekolah Dasar - Saifudin Saifudin; Rachmat Imam Muslim; Ade Bagus Primadoni (Lembaga Bale Literasi, 2026)
This research aims to improve the collaboration skills and scientific literacy of fifth-grade elementary school students through the implementation of the STEM (Science, Technology, Engineering, and Mathematics) approach in science learning. The study employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 25 fifth-grade students from a public elementary school. Data were collected through observations, scientific literacy tests, documentation, and teacher reflection notes. Collaboration skills were measured using observation sheets, while scientific literacy was assessed through tests based on OECD indicators, including explaining scientific phenomena, evaluating and designing scientific investigations, and interpreting scientific data and evidence. The results showed a gradual improvement in students’ collaboration skills and scientific literacy from the pre-cycle to the second cycle. The percentage of students categorized as good and very good in collaboration skills increased from 32% in the pre-cycle to 76% in the second cycle. Meanwhile, the proportion of students achieving high and very high levels of scientific literacy rose from 40% to 80%. These findings indicate that the STEM approach is effective in fostering collaborative, contextual, and meaningful learning experiences. Therefore, the STEM approach is recommended as an alternative strategy in elementary science education to enhance students’ collaboration skills and scientific literacy.